PENGARUH KOMPENSASI FINANSIAL DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA KAMPAR BANGKINANG KOTA - Rahmadani, Febi; Ningsih, Dewita Suryati; Wasnury, Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze influence financial compensation and working environment for employee morale on the regional water company (PDAM) Tirta Kampar Bangkinang town. Populasi of this research is all employees regional water company (PDAM) Tirta Bangkinang Kampar town. The method used is a census by using the 57 respondents. This data retrieval by giving questionnaires to respondents. In terms of data analysis, this study using path analysis with the help of SPSS version 17.0.The result of this study indicate that the compensation effect on employee morale at the Regional Water Company (PDAM) Tirta Bangkinang Kampar town, the satisfied employees of the compensation received by the morale will increase and vice versa. Work environment affects the employee morale at the Regional Water Company (PDAM) Tirta Bangkinang Kampar town. More conducive working environment then morale will increase and vice versa. Compensation and working conditions affect the morale of employees in the Regional Water Company (PDAM) Tirta Kampar Bangkinang city, donations compensation and work environment influence on morale was at 49.8%. compensation effect on employee morale through working environment on regional water companies (PDAM) Tirta Bangkinang Kampar town.Keywords: Financial compensation, work environment, morale.